1987
DOI: 10.1093/ajcp/88.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Recurrence and Survival of Patients with Breast Cancer

Abstract: In this study, the characteristics of 646 patient's primary breast carcinomas, including histologic grade (HG), nuclear grade (NG), mitotic grade (MG), final grade (FG), estrogen receptor (E2R) status, and patient's lymph node status (LN) at the time of surgery were correlated with recurrence-free interval and patient survival in order to determine whether any one parameter or group of parameters serve as adequate predictors of tumor behavior and, therefore, patient's prognosis. The authors' results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
23
1
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(34 citation statements)
references
References 0 publications
8
23
1
2
Order By: Relevance
“…The reliability of our results is further strengthened by the identification of the axillary lymph node and hormone receptor status as independent prognostic factors for overall and disease-free survival. These parameters confirm the observations of the studies cited above as well as those from other investigations (Nemoto et al, 1980;Baak et al, 1985;Bryan et al, 1986;Fisher et al, 1987;Russo et al, 1987;Todd et al, 1987;Chevallier et al, 1988).…”
Section: Immunohistologysupporting
confidence: 91%
See 1 more Smart Citation
“…The reliability of our results is further strengthened by the identification of the axillary lymph node and hormone receptor status as independent prognostic factors for overall and disease-free survival. These parameters confirm the observations of the studies cited above as well as those from other investigations (Nemoto et al, 1980;Baak et al, 1985;Bryan et al, 1986;Fisher et al, 1987;Russo et al, 1987;Todd et al, 1987;Chevallier et al, 1988).…”
Section: Immunohistologysupporting
confidence: 91%
“…Sidky & Walker (1984) observed that histologically poorly differentiated carcinomas stained less for P2m- Zuk & Walker (1987) demonstrated a correlation between tumour grading and the expression of P2m and HLA-A,B,C. Regarding the prognostic value of tumour grading for breast cancer patients (Bloom & Richardson, 1957;Freedman et al, 1979;Haybittle et al, 1982;Reiner et al, 1985;Russo et al, 1987;Chevallier et al, 1988) (UICC, 1987; Table I). The identification of independent prognostic effects of MHC antigen expression was assessed by the Cox multivariate regression analysis.…”
mentioning
confidence: 97%
“…Six studies were conducted on node-negative carcinomas, 26-31 13 on mixed node-negative/positive carcinomas, 8,16,[32][33][34][35][36][37][38][39][40][41][42] and two on node-positive carcinoma. 42,43 Architecture (tubularity) was the primary independent predictor in three, 27,29,43 nuclear pleomorphism by subjective assessment in two, 33,35 morphometric measurements of nuclear area in one, 36 and mitotic count in eight studies.…”
Section: Relative Importance Of Components Of Bloom-richardson Gradementioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] However, only few studies from India are present. [16][17][18][19] and to the best of our knowledge, no study from Western Rajasthan regarding the clinico-histological parameters of breast cancer is available.…”
Section: Introductionmentioning
confidence: 99%